Analisis Mekanisme Kurikulum dan Evaluasi (Aphasia) serta (Diskalkulia) pada Siswa Kelas 1 SDN Sukasari 5 Kota Tangerang - Septy Nurfadhillah; Alfira Fazriandina; Amilanadzma Hidayah; Niken Nur Yolawati; Nurlaili Maghfiroh; Nurul Dwi Arlita; Roro Rachmi Dewanti (ANWARUL, 2021)
This research uses qualitative research. The data collection technique in this research is by conducting interviews, documentation and observations of class I (a) and I (b) teachers as well as accompanying teachers for children with special needs and school principals. The research was conducted to find out how the mechanism of curriculum and evaluation regarding language/communication difficulties and learning difficulties in mathematics. The method given by the teacher to children with special needs who have language/communication difficulties is the same as other students as well as students who have difficulty learning mathematics. The assessments are given both in terms of academic and non-academic. Assessments are made for children with special needs to see the child's initial abilities, after which the PPI program is made. And in the evaluation process the teacher will review every observation made when students face other difficulties. The conclusions obtained by the researcher are, the curriculum applied by SDN Sukasari 5 Tangerang City is a regular curriculum with a modification of the PPI program. The assessment is carried out before the acceptance of students in the new school year with indications that have been notified to the teacher from the students' parents.